2021
DOI: 10.2215/cjn.15080920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Exercise on Dialysis-Related Symptoms in Individuals Undergoing Maintenance Hemodialysis

Abstract: BackgroundHemodialysis is associated with a high symptom burden that impairs health-related quality of life and functional status. Effective symptom management is a priority for individuals receiving hemodialysis. Aerobic exercise may be an effective, nonpharmacologic treatment for specific hemodialysis-related symptoms. This systematic review investigated the effect of aerobic exercise on hemodialysis-related symptoms in adults with kidney failure undergoing maintenance hemodialysis.Design, setting, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 42 publications
1
30
2
2
Order By: Relevance
“…There is evidence in the haemodialysis population that both depression and anxiety (including stress and worry), as well as general mental health, are improved with aerobic exercise. 59,60 In the PD population, there is evidence that physical activity in people receiving PD improves general mental health. 55,61,62…”
Section: Evidence And/or Clinical Experiencementioning
confidence: 99%
“…There is evidence in the haemodialysis population that both depression and anxiety (including stress and worry), as well as general mental health, are improved with aerobic exercise. 59,60 In the PD population, there is evidence that physical activity in people receiving PD improves general mental health. 55,61,62…”
Section: Evidence And/or Clinical Experiencementioning
confidence: 99%
“…As such, it is plausible that preemptive KT recipients may achieve better physical performances than patients requiring prolonged dialysis before transplant. On the other hand, recent studies have demonstrated that physical aerobic exercise can exert various beneficial effects on many clinical outcomes, both in patients with CKD and under dialysis [ 13 , 14 ].…”
Section: Physical Activity Before and After Kidney Transplantationmentioning
confidence: 99%
“…Patients on hemodialysis with a greater number of comorbidities have been reported to have more severe depression, higher levels of anxiety [ 6 ], and higher fatigue scores [ 7 ] than those with fewer comorbidities. Studies have revealed that exercising mitigates anxiety, depression, and fatigue in patients on hemodialysis [ 8 ]. However, more evidence is required to verify the role of exercise in relieving the psychological distress of patients on hemodialysis with comorbidities.…”
Section: Introductionmentioning
confidence: 99%